2008
DOI: 10.1089/pho.2007.2180
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Changes and Removal of Debris on Apical Dentin Surfaces after Nd:YAG Laser and Diode Laser Irradiation

Abstract: Both lasers promote morphologic changes and debris removal. These alterations of the dentin surface appeared to be more evident in the Nd:YAG laser group, but the diode laser group showed more uniform changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
3
17
0
5
Order By: Relevance
“…These findings are not to be confused with the study of de Moura-Netto et al 16 in which Nd:YAG lasing improved apical marginal sealing in EDTA-T rinsed canals, as roots with open apices of an ISO size 40 were evaluated. All studies mentioned so far, however, attribute lower leakage rates to the more evident changes in dentin walls with use of the Nd:YAG, as stated by de Mouro-Netto et al 8 The findings of the present study are also in line with those of Gurbuz et al, 32 which reported no significant differences in root canal wall cleanliness between root canals rinsed with EDTA and those lased with the Nd:YAG laser. Furthermore, the latter study supported that EDTA rinsing is not efficient for cleaning the apical third.…”
Section: Meire Et Alsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are not to be confused with the study of de Moura-Netto et al 16 in which Nd:YAG lasing improved apical marginal sealing in EDTA-T rinsed canals, as roots with open apices of an ISO size 40 were evaluated. All studies mentioned so far, however, attribute lower leakage rates to the more evident changes in dentin walls with use of the Nd:YAG, as stated by de Mouro-Netto et al 8 The findings of the present study are also in line with those of Gurbuz et al, 32 which reported no significant differences in root canal wall cleanliness between root canals rinsed with EDTA and those lased with the Nd:YAG laser. Furthermore, the latter study supported that EDTA rinsing is not efficient for cleaning the apical third.…”
Section: Meire Et Alsupporting
confidence: 91%
“…1 A variety of studies have shown that direct Nd:YAG laser irradiation on dentin surfaces produces melting and recrystallization which, in turn, causes a reduction in dentin permeability. [2][3][4][5][6][7][8] In view of ''dentin melting'' 9 and ''reduction of the permeability of dentin'' 4 a number of investigators have attempted to improve the quality of the apical seal and thus reduce apical leakage following apical filling. [10][11][12][13][14][15][16] Apparently, morphological changes following Nd:YAG laser irradiation can influence the marginal sealing of the root canal obturations.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7]13 These changes are confirmed on the SEM images in this study in Group 3 with Nd:YAG lasing, after the NaOCl supported root-canal preparation (Fig. 3a).…”
Section: S-46supporting
confidence: 75%
“…An abundant number of studies have shown that direct Nd:YAG laser irradiation on dentin surfaces produces melting and recrystallization, which, in turn, causes a reduction in dentin permeability. [1][2][3][4][5][6][7] In view of ''dentin melting'' 8 and ''reduction of the permeability of dentin'', 3 a number of investigators have attempted to improve the quality of the apical seal and thus to reduce apical leakage after apical filling. [9][10][11][12][13][14][15] It is clear from these studies that morphologic changes after Nd:YAG laser irradiation can influence the marginal sealing of the root-canal obturation.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] As an adjunct in endodontic treatment, the use of high intensity laser devices has demonstrated significant intracanal disinfection and morphological changes of the dentin surface that interfere with dentin permeability and root canal sealing. 5,6,[8][9][10][11][12][13][14][15][16] The interaction between laser wavelengths and irradiated tissues will assume the level of energy absorbed by the latter and therefore the intensity of tissue alteration. 3,9,11-,15-18 Wavelengths between 800 and 1100 nm (i.e., diode and Nd:YAG lasers) have poor interaction with dental hard tissues like enamel and dentin.…”
Section: Introductionmentioning
confidence: 99%